Local scour at wide bridge piers - Ahmad, Nordila; Mohammed Ali, Thamer Ahmed; Ali, Faisal; Yusuf, Badrunnisa (ESRSA Publication, 2014)
Laboratory data for local scour depth at the size of wide piers are presented. Clear water scour tests were performed various pier widths (0.06, 0.076, 0.102, 0.14 and 0.165 m), two type of pier shapes (circular and rectangular) and two types of uniform cohesionless bed sediment (d50 = 0.23 and d50 = 0.80 mm). New data are presented and used to demonstrate the effects of pier width, pier shape and sediment size on scour depth. The influence of equilibrium time (te on scouring processes also discussed. Equilibrium scour depths were found to decrease with increasing values of b/d50. The temporal development of equilibrium local scour depth with new laboratory data is demonstrated for flow intensity = 0.95. On the other hand, the result of scour mechanism have shown a significant relationship between normalized volume of scoured and deposited with pier width, b. The experimental data obtained in this study and data available from the literature for wide piers are used to evaluate predictions of existing methods.